2014
DOI: 10.1021/jf5042678
|View full text |Cite
|
Sign up to set email alerts
|

Antioxidant and Antimicrobial Properties of Wine Byproducts and Their Potential Uses in the Food Industry

Abstract: Evaluation of the total antioxidant capacity of solid matrices without extraction steps is a very interesting 10 alternative for food researchers and also for food industries. These methodologies have been denominated by QUENCHER from 11 quick, easy, new, cheap, and reproducible assays. To demonstrate and highlight the validity of QUENCHER (Q) methods, values 12 of Q-method validation were showed for the first time, and they were tested with products of well-known different chemical The most commonly applied i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
78
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 101 publications
(87 citation statements)
references
References 63 publications
7
78
0
2
Order By: Relevance
“…The intensive accumulation of Pb in the pomace can limit the re‐use of this by‐product as a fertiliser or subsequent extractions for other purposes (e.g. cosmetic products) …”
Section: Discussionmentioning
confidence: 99%
“…The intensive accumulation of Pb in the pomace can limit the re‐use of this by‐product as a fertiliser or subsequent extractions for other purposes (e.g. cosmetic products) …”
Section: Discussionmentioning
confidence: 99%
“…The products obtained from vinasse, in most of the cited studies (Table 4), involve the production of nutritional microbial media, tartaric acid, protein rich biomass and plant growth substrates [101,102]. It has been reported that non treated vinification lees may be used either alone or combined with other cheap waste products, such as corn steep liquor, to formulate inexpensive nutrient media to be used for fermentative production of lactic acid or xylitol [103].…”
Section: Utilisation Of Vinasse As Substratementioning
confidence: 99%
“…The antioxidant properties of grape parts, products and byproducts is well known, including their chelating activities, high radical scavenging properties in relation to Trolox and Vitamins C and E [27] and the potential to inhibit lipid oxidation in various food and cell models [8,27,28]. The consumption of grape-derived dietary flavonoids in the form of grape extracts and grape seed powders has been shown to effectively suppress oxidative stress and prevent oxidative damage in vivo [29].…”
Section: Antioxidant and Antiagingmentioning
confidence: 99%
“…The lower efficiencies found at higher concentrations of the extract was caused by its poor dissolution in water [27]. Products derived from seed-free wine pomace showed bactericidal effects against total aerobic mesophilic bacteria and lactic acid bacteria and inhibited Enterobacteriaceae and the product derived from whole winery products presented bacteriostatic activity against these microorganisms [8]. Grapeseed extracts were active against Alicyclobacillus acidoterrestris vegetative cells and spores [57], and against Listeria monocytogenes [29].…”
Section: Antimicrobialmentioning
confidence: 99%